Physical properties of aqueous solutions of potassium l-prolinate from 298.15 to 343.15 K at atmospheric pressure - Shaikh, M.S. (Springer International Publishing, 2017)
In this paper, experimental physical properties such as density, refractive index, and viscosity of aqueous potassium l-prolinate (KPr) as a solvent for CO2 capture were investigated. Different concentrations of aqueous KPr in terms of mass fractions (0.05, 0.10, 0.20, 0.30, and 0.40) were studied over a temperature range 298.15-343.15 K. The obtained results showed that all physical properties increase with increasing the concentration of the solution (isothermally), and decrease as the solution temperature rises for any given concentration. The experimental data of density, refractive index, and viscosity were correlated using empirical correlations as a function of both, temperature and concentration. Coefficient of thermal expansion and activation energy were calculated from the experimental density and viscosity data, respectively, in the same temperature range. Thermal expansion coefficient slightly increases with increase in the temperature and concentration, while activation energy increases with the rise in concentration of amino acid salt. © 2016 Institute of Chemistry, Slovak Academy of Sciences.